Jumlah Inang Dan Kepadatan Parasitoid: Pengaruhnya Terhadap Perilaku Selfsuperparasitism Parasitoid Trichogramma chilotraeae Nagaraja & Nagarkatti (Hymenoptera: Trichogrammatidae) - Hasriyanty Hasriyanty (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
The aim of the research was to identify the influences of the number of hosts and the density of parasitoid on the behavior of selfsuperparasitism at Trichogramma chilotraeae. The behavior of selfsuperparasitism was studied by examining the percentage of selfsuperparasitism as affected by the variability of host number (3, 6, 12, 24 and 48) exposed to 1 and 2 female parasitoids. A descriptive analysis was conducted in order to identify an ovipositioning sequence. The results indicated that the number of hosts significantly affected the selfsuperparasitism percentage in the exposing treatments 1 and 2. The percentage of selfsuperparasitism was positively correlated with the ratio of the host number and the female parasitoid density. The tendency of the selfsuperparasitism behavior occurred in the early stage of ovipositioning. .